THE EFFECT OF MASASE COUNTERPRESSURE ON LABOR PAIN KALA ONE ACTIVE PHASE IN MOTHER BIRDS IN BPM SETIA - Hadriani, Hadriani; Purwaningsih, Eka (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective: Labor pain can cause stress which can cause excessive hormone release such asketocolamine and steroids. Pain can be reduced by pharmacological techniques and non-pharmacologicaltechniques. Pharmacological techniques using analgesic drugs, while non-pharmacological techniques arepain control by using counterpressure techniques that reduce pain sensations by inhibiting pain from thesource. The purpose of this study was to determine the effect of counterpressure massage on labor pain kalaone active phase in maternity at BPM Setia. Material and Method: This research is Quasi Experimentalwith one group pretest and posttest design with a population of all mothers giving birth during the activephase at Setia BPM and a sample of 15 respondents. Data analysis using the Wilcoxon Signed Rank Test.Result: The scale of pain before counterpressure massage was performed in the first phase of activematernity, 9 respondents (60.0%) experienced severe pain, moderate pain as many as 3 respondents (20%)and very severe pain 3 respondents (20%). The scale of pain after counterpressure massage, mild pain 2respondents (13.3%), moderate pain 9 respondents (60.0%) and experiencing severe pain 4 respondents(26.7%). The bivariate analysis showed p-value = 0,000. Conclusion: There were significant differences inpain before and after counterpressure massage in the first maternal phase of active at Setia BPM.Suggestions for midwives to be able to apply counterpressure massage techniques to reduce labor pain whenI am the active phase of maternity.